Analisis Balanced Scorecard Pada Pabrik Garmen (Kasus:Pt. Handsumtex)“ - William William (Universitas Tarumanagara, 2019)
A marketing strategy is a way of introducing a company in a form or service with a competitive advantage over an existing competitor. Marketing strategy is often used as a reference to prepare the company plan, which from the reference can be poured into careful planning to be used as an idea of the company to run business activities. Garment industry is a fast growing industry due to the technology and demand from consumers in accordance with the era of globalization.This research has a purpose to get an idea about marketing strategy to improve competitiveness, and to know how effective execution of marketing strategy that have been done. This research was conducted at PT. Handsumtex, from internal and external factors will be made Balanced Scorecard analysis. Data collection techniques with documentation, interviews and observation, descriptive research. The results of the effectiveness analysis of marketing strategy shows an increase in total sales from year to year and serve as a reference to the effectiveness of marketing strategies in competition between garment factories.